Nutrition, Epigenetics, and Major Depressive Disorder: Understanding the Connection - Ortega, Miguel A.; Fraile-Martínez, Óscar; García-Montero, Cielo; Alvarez-Mon, Miguel Angel; Lahera, Guillermo; Monserrat, Jorge; Llavero-Valero, Maria; Mora, Fernando; Rodríguez-Jiménez, Roberto; Fernandez-Rojo, Sonia; Quintero, Javier; Alvarez De Mon, Melchor (Frontiers in Nutrition, 2022)
Major Depressive Disorder (MDD) entails a multifactorial disorder of rising prevalence. Nearly 280 million people suffer from this leading cause of disability in the world. Moreover, patients with this condition are frequently co-affected by essential nutrient deficiency. The typical scene with stress and hustle in developed countries, tends to be accompanied by eating disorders implying overnutrition from high carbohydrates and high fat diets with low micronutrients intake. In fact, nowadays, COVID-19 pandemic has drawn more attention to this underdiagnosed condition, besides the importance of nutritional status in shaping immunomodulation, in which minerals, vitamins or omega 3 polyunsaturated fatty acids (ꞷ-3 PUFA) play an important role. The awareness of nutritional assessment is greater and greater in the depressed patient since antidepressant treatments have such a significant probability of failing. As diet is considered a crucial environmental factor, underlying epigenetic mechanisms that experience an adaptation or consequence on their signaling and expression mechanisms, are reviewed. Here we include metabolic changes derived from an impairment in cellular processes due to lacking some essential nutrients in diet and therefore in the organism. Finally, aspects related to nutritional interventions and recommendations are also addressed.